One-pot synthesis of pyrimidine linked naphthoquinone-fused pyrroles by iodine-mediated multicomponent reactions. Issue 26 (23rd June 2020) - Panday, Anoop Kumar; Ali, Danish; Choudhury, Lokman H.
Abstract : Herein we report iodine-mediated novel three-component reactions for the synthesis of naphthoquinone-fused pyrroles linked with a barbituric acid moiety. Abstract : Herein we report iodine-mediated multicomponent reactions for the synthesis of naphthoquinone-fused pyrroles tethered with a pyrimidine moiety. The reaction of aryl methyl ketones (3 ) or terminal aryl alkynes (5 ) in the presence of molecular iodine in DMSO medium followed by sequential addition of barbituric acids (2 ) and 2-amino-1, 4-naphthoquinone (1 ) provides the corresponding three-component hybrid molecules 4 having naphthoquinone-fused pyrroles tethered with a barbituric acid moiety. This three-component reaction proceeds via metal-free C–H oxidation followed by multi-component cyclization forming three new bonds (2 C–C, 1 C–N) in one pot. Alternatively, the same molecules can also be prepared from the reaction of arylglyoxals, 2-aminonaphthoquinone, and barbituric acids in the presence of a catalytic amount of iodine in methanol medium under reflux conditions. The salient features of these methodologies are: one-pot metal-free method, good yields, wide substrate scope, easy purification of products, and the presence of medicinally important naphthoquinone, pyrrole and pyrimidine moieties in the products.